Arthritis sternoclavicularis jako prícina mediastinitidy - Hromádka, P; Cernohorský, S (Rozhledy v chirurgii, 2011)
Sternoclavicular arthtritis is a condition of the joints and movement apparatus which is treated by Rheumatologists and Orthepedists. Incorrect or late treatment of this condition leads to the development of septic arthritis and overall complications. This report describes three rare cases of mediastinitis caused by inflammation of the sternoclavicular joint. The authors analyze the possibilities of surgical treatment and early diagnosis.
Keywords: Arthritis, Infectious; Mediastinitis; Sternoclavicular Joint; Female; Aged; Adult; dospělí; Humans; ženské pohlaví; mužské pohlaví; senioři; lidé; sternoklavikulární kloub; lidé středního věku; infekční artritida; Male; Middle Aged; mediastinitida